(3GdefJbi ef cJGH edM GdedM aj GdJLfjSs - (3GdMVjQjs ((3Ydi Hf CHj WGdH Hf Ydi Hf SYjO Hf GdNTGH GdMdHi s)
(3ChdgG (B:s
(3GdMeO ddg eOjQ Gdadc GdOhGQ bGd GdMVjQi QMeg Gddg EYde Cf GdcdGe GdeYJOd HfGA GdeJhGRf CLRGA dg KdK eQGJH jfbSe Edi KdGKI CbSGe GdeJhGRf hGdeSLY hGdeQUY s
(3BNQgG (B:s
(3hbGd GdeSJhai (B:- (3TQHJ GdOhGA agfjJg hCdHSJ ef TQHg GdYGajI hdGRGd LSec ai UMI hBKGQ CSbGjg YGajg fLR GdeNJGQ HMeO Gddg hefg hJhajbg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3HdGZI (B344) s
Keywords: (3GdCOHs